Enhancing Customers’ Purchase Decisions Making of PT. Pelni Through Service Quality and Price - Taffarel Parikesit; Kelvin Aditya; Ovalia Rukmana; Prima Widiyanto (Dinasti Review, 2025)
The purpose of this study is to investigate factors that can enhance purchase decision making of PT PELNI. The target population of this study is PT PELNI’s customers; A non-probability sampling with purposive sampling technique adopted in this study with 52 numbers of respondents. Questionnaires were distributed to grasp the respondents’ perception on the impacts of service quality, price, and facilities on purchasing decisions of PT PELNI. The data were analyzed using multiple linear regression with SPSS version 26. The results showed that service quality has a positive and significant effect on purchasing decisions, and so does price. However, facilities do not have positive and significant effect to the purchase decision. Additionally, the findings indicated that those variables investigated simultaneously have significant effect to the purchase decision.